Design for good - a mobile application to encourage Singaporeans to be more active - Lee, Jia Zhi (Nanyang Technological University, 2022)
This “Design for Good” project aims to develop an application to improve users’ life through understanding with empathy. Previously, a mobile app prototype “Life Feed” was designed using a design-thinking methodology to encourage NTU students to eat healthy. However, due to the COVID-19 situation, the results of whether the users are able to make better food choices cannot be concluded. This project hopes to continue to design a mobile application to improve users’ life and to develop it using cross-platform development frameworks such as ReactNative or Flutter.